Penyuluhan Edukasi Pola Makan Bergizi Pada Masyarakat Untuk Pencegahan Dini Stunting - Tosi Rahmaddian; Irwadi Irwadi; Muhammad Rizki Saputra; Nurmaines Adhyka; Novia Zulfa Hanum; Intan Kamala Aisyiah (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2025)
Stunting is a chronic nutrition issue characterized by height below the standard for a child’s age. According to the 2018 Basic Health Research (Riskesdas), the prevalence of stunting in Indonesia reached 30.8%, significantly higher than the government’s target of below 20% by 2024. One of the primary causes of stunting is inadequate nutrition, particularly during the first 1,000 days of life, which can impede growth and development, resulting in long-term health and cognitive issues. To address this, comprehensive prevention efforts are essential, including community education on nutritious eating. This Community Service initiative targets community leaders and the public, especially mothers and expectant mothers in the Nagari Sago Salido area. The methods employed include distributing questionnaires, presenting educational materials, facilitating discussions, conducting anthropometric screenings for toddlers, and providing nutritious food for participants. The aim is to enhance community understanding of the importance of nutritious diets and their impact on child growth, while encouraging healthier eating habits within families. This initiative seeks to foster sustainable changes in dietary practices and contribute to the reduction of stunting rates in the region.